Ethnomusicology : Its Role, Power and Significance in the Humanities - Makubuya, James K. (The Charles D. LaFollette Lecture Series, 2019)
In this 40th LaFollette lecture, I start by addressing the fact that in the course of time, the music discipline became divided into four different academic sub-disciplines including: Music Theory and Composition, Historical Musicology, Ethnomusicology, and Electronic Music. I discuss the fact that it was in the 1950’s CE, when many global scholars collaborated and were in total agreement that “ethnomusicology” will be used from then on, as a forum for a very effective academic approach for learning and understanding “the study of music in its social and cultural context”. Since then, this interdisciplinary ethnomusicology discipline has been and continues to be studied through its role and power in the lives of people. This is done by looking at and studying as well as analyzing a number of humanistic elements that among others include linguistics, aesthetics, ethics, mental health, social organizations, etc., etc. The analytical examination of all those, definitely confirm the deep role, the power and significance the ethnomusicology sub-discipline plays in the humanities. The LaFollette Lecture Series was established by the Wabash College Board of Trustees to honor Charles D. LaFollette, their longtime colleague on the Board. The lecture is given each year by a Wabash College Faculty member who is charged to address the relation of his or her special discipline to the humanities broadly conceived